Intracholecystic papillary-tubular neoplasm of gallbladder: A 5-year retrospective pathological study - Prabir Hazarika; Manoj Kumar Sharma (Wolters Kluwer Medknow Publications, 2018)
Background: Intracholecystic papillary-tubular neoplasm (ICPN) is a relatively new entity which includes neoplastic polyps, adenomas, and papillary neoplasms that are ≥1.0 cm. This study is done to evaluate the pathological features of ICPN and to find out the factors associated with invasion. Materials and Methods: This is a 5-year retrospective study in a referral pathology center. A total of 19 cases of ICPN are found. The cases are analyzed for age and sex distribution, clinical suspicion, stages, histological architecture, differentiation, and grade of dysplasia. Descriptive statistics and test of significance by Chi-square and t-test are used in the study. Results: ICPN comprises 23.5% of all gallbladder neoplasms. Two-thirds of the cases were suspected radiologically. Age range is 26-65 years with mean age of 50 years. They are 2.8 times more common in female. Approximately one-third of the cases show invasion. The most common histological pattern is papillary, followed by papillary-tubular and finally by tubular pattern. Pyloric and biliary are the most common differentiation pattern followed by oncocytic and intestinal pattern. About three-fourths of the cases are associated with high-grade dysplasia mostly diffuse high-grade dysplasia. Conclusion: We have found the younger age of presentation, less proportion of invasive tumors, fewer tumors with biliary phenotypes, and fewer tumors with high-grade dysplasia as compared to previous studies. Factors significantly associated with invasion are grade and extent of dysplasia particularly diffuse high-grade dysplasia.